Effectiveness of Prototype Curriculum Policy in Mathematics Learning - Alyan Fatwa (Ilmu Inovasi Nusantara, 2023)
This research involved one class as an experimental class to determine the effectiveness of the Prototype Curriculum Policy in Mathematics Learning at SMP Negeri 2 Kajen, Pekalongan Regency. The research design used was a group pretest-posttest design. The main problem in this research is whether the prototype curriculum policy is effectively implemented in mathematics learning for class VII students at SMP Negeri 2 Kajen. This type of research is pre-experimental research. The research results show that: (1) The average score of students' mathematics learning outcomes before the prototype curriculum was implemented in mathematics learning was 22.8 and was deficient. These results showed that 25 students, or 100%, had yet to reach the KKM, which meant that classical completion had not been achieved. (2) The average score of students' mathematics learning outcomes after implementing the mathematics learning prototype curriculum is 85 and is in the high category. These results found that 24 out of 25 students, or 96% achieved the KKM, which means that classical completion was achieved. (3) The average percentage of student activity is 83%, if it is linked to the student activity criteria, namely 75%, then student activity reaches the active criteria. (4) The student response questionnaire showed that 97% responded positively to mathematics learning. From the research results above, it is concluded that the prototype curriculum policy for mathematics learning is effectively implemented at SMP Negeri 2 Kajen, Pekalongan Regency